Rancang Bangun Sistem Informasi Penyewaan dan Rekomendasi Lahan Pertanian Menggunakan Metode KNN - Natasya, Natasya; Noratama Putri, Ramalia (Jurnal SANTI - Sistem Informasi dan Teknik Informasi, 2024)
Agriculture plays a crucial role in the economy of Indonesia, particularly in Kampar Regency, Riau Province. The agricultural, forestry, and fisheries sectors serve as the backbone in forming the Gross Regional Domestic Product (GRDP), making a significant contribution to the national economy. However, farmers in Karya Indah Village face challenges in finding and renting agricultural land that meets their needs. To address this challenge, the development of a web-based agricultural land rental information system is essential. This research aims to design a web-based information system using the K-Nearest Neighbor (KNN) algorithm to provide recommendations for agricultural land suitable for farmers' needs. This system facilitates farmers in finding and renting suitable agricultural land, while landowners can efficiently offer their land for rent. The research not only aims to improve efficiency in the process of renting agricultural land but also to enhance agricultural productivity and farmers' income. The research findings indicate that the KNN method can provide accurate recommendations for agricultural land, thus helping to improve farmers' welfare and the overall sustainability of the agricultural sector. The research findings show that the KNN method can recommend agricultural land with an accuracy rate of 80%.